Computer organization and architecture designing for performance - Stallings, William (Pearson Education, 2003)
For junior/senior/graduate-level courses in Computer Organization in departments of Computer Science and Computer Engineering. This text provides a clear, comprehensive presentation of the organization and architecture of modern-day computers, emphasizing both fundamental principles and the critical role of performance in driving computer design. The text conveys concepts through a wealth of concrete examples highlighting modern CISC and RISC systems.